Predators' consumption of unpalatable prey does not vary as a function of bitter taste perception. (3rd December 2019) - Hämäläinen, Liisa; Mappes, Johanna; Thorogood, Rose; Valkonen, Janne K; Karttunen, Kaijamari; Salmi, Tuuli; Rowland, Hannah M
Abstract: Many prey species contain defensive chemicals that are described as tasting bitter. Bitter taste perception is, therefore, assumed to be important when predators are learning about prey defenses. However, it is not known how individuals differ in their response to bitter taste, and how this influences their foraging decisions. We conducted taste perception assays in which wild-caught great tits ( Parus major ) were given water with increasing concentrations of bitter-tasting chloroquine diphosphate until they showed an aversive response to bitter taste. This response threshold was found to vary considerably among individuals, ranging from chloroquine concentrations of 0.01 mmol/L to 8 mmol/L. We next investigated whether the response threshold influenced the consumption of defended prey during avoidance learning by presenting birds with novel palatable and defended prey in a random sequence until they refused to attack defended prey. We predicted that individuals with taste response thresholds at lower concentrations would consume fewer defended prey before rejecting them, but found that the response threshold had no effect on the birds' foraging choices. Instead, willingness to consume defended prey was influenced by the birds' body condition. This effect was age- and sex-dependent, with adult males attacking more of the defended prey when their body condition was poor, whereas body condition did not have an effect on the foraging choices of juveniles and females. Together, our results suggest that even though taste perception might be important for recognizing prey toxicity, other factors, such as predators' energetic state, drive the decisions to consume chemically defended prey. Abstract : Individual differences in predators' bitter taste perception do not influence the consumption of chemically defended prey. Many prey species have bitter-tasting defenses that generate aversive responses in predators. We show that great tits vary in their response to bitter taste, but this does not influence the number of novel defended prey they attack during avoidance learning. This suggests that other factors, such as the current physiological state, have a larger impact on predators' foraging decisions.